OUTCOME OF SEVERE/CRITICAL COVID-19 INFECTION IN PATIENTS WITH AND WITHOUT DIABETES MELLITUS - Bilal Saeed; Abdul Rehman Arshad (Khyber Medical University Journal, 2021)
OBJECTIVES: To compare outcomes of COVID-19 infection in patients with and without diabetes mellitus (DM).